Reframing English Studies in India: Socio-Psycholinguistic Issues - Kumar Sharma, Susheel (East European Journal of Psycholinguistics, 2022)
The paper deals with the theory and praxis of decolonising English Studies in India. The paper suggests appropriate measures to pull out English studies from the Macaulayan paradigm and to recast the priorities in English Studies in the light of changing role for emerging India in the unipolar world realities, rising aspirations of the middle classes, democratic and egalitarian needs. The project of ‘decolonising’ education at the macro-level and English Studies at the micro-level has been discussed with reference to curriculum, teaching methods, materials, evaluation, research and publication and medium of instruction in all possible details in the paper. The paper attempts to deal with contemporary realities like various treaties and market economy and issues like making a distinction between real knowledge and colonial knowledge along with historical context of English Studies. Several measures have been suggested to make English Studies in India relevant to the contemporary times, to save them from being derivative and to reshape Euro-American knowledge about English culture, Literature and Language from Indian perspective. Practical suggestions to decolonise curriculum have been made keeping in view the distinction between teaching literature and language in the first and the second language situations.
Keywords: curriculum, decolonisation, education, English literature/ language, Gandhi, India, Macaulay, publications, research, teaching methods.